The Relationship Between the Intensity of Watching Islamic Preaching on Social Media and the Religious Attitudes of University Students - Nurrahmi, Dwi; Surawan, Surawan; Arifani, Suci (Proceeding International Conference on Religion, Science and Education, 2025)
Social media is a digital platform that can facilitate the process of disseminating information quickly. Social media is a form of technological development that is widely known by people of all ages. Along with the development of technology, several things have changed, not least in the realm of religion. In today's technological era, da'wah can also be done through social media in the form of images, motivational words, videos and others. The use of social media in everyday life allows it to have an influence on a person's positive and negative attitudes. The purpose of this study is to determine the relationship between the intensity of watching Islamic da'wah shows on social media with the religious attitudes of the Islamic student education FTIK IAIN Palangka Raya. The method used is quantitative with a correlational type. Data collection techniques using questionnaires and documentation. The data analysis technique uses the mean formula, Pearson Product moment correlation, and the coefficient of determination using SPSS 18. The results of this study indicate: (1) The intensity of watching Islamic da'wah shows of Islamic student education FTIK IAIN Palangka Raya on social media is 3, 54 is in the high category. (2) The religious attitude of the Islamic student education FTIK IAIN Palangka Raya is 3.87, which is in the high category. (3) There is a positive relationship between the intensity of watching Islamic da'wah shows on social media and the religious attitude of the Islamic student education FTIK IAIN Palangka Raya with a correlation coefficient value of 0.692 which is included in the strong relationship category. (4) The effect of the intensity of watching Islamic da'wah shows on social media on the religious attitudes of the Islamic student education FTIK IAIN Palangka Raya was 47.8%.